(untitled) (Medical Forum Monthly, 2024)
Objective: The current study was done to pilot different techniques of making lectures interactive and to find out compliance of the students with interactive lectures. Study Design: Prospective / comparative study. Place and Duration of Study: This study was carried out at the Department of Pharmacology, Aziz Fatima Medical & Dental College, Faisalabad from 01.04.2014 to 30.04.2014 Materials & Methods: An entire class of 3rd year MBBS students (n = 65) was given interactive and the regular lectures for the Drugs acting on The Central nervous system in Pharmacology. Out of the total number of 12 lectures, alternative lectures were delivered in an interactive style. At the end of 12 lectures, students’ opinion was obtained using a structured feedback evaluation questionnaire, having 5 statements on a 5 point Likert scale. Results: 92% of the students found that interactive lectures are more effective. Notably more number of students agreed or strongly agreed that interactive lectures amplified alertness, developed interest, by-passed monotony, and urged them to learn by themselves as compared to usual lectures. The students preferred use of video-clips (65%), followed by each-one-teach-one. The use of interactive lectures to create interest among students is supported by the results of the study. Conclusion: An interactive lecture was more easily listened and considered to be more useful than the regular lecture by the students